2007
DOI: 10.1002/imhj.20127
|View full text |Cite
|
Sign up to set email alerts
|

It takes time: Impacts of Early Head Start that lead to reductions in maternal depression two years later

Abstract: The Early Head Start Research and Evaluation Project, a random-assignment evaluation, found a broad pattern of positive impacts for children and families. However, there were no program impacts on depression or use of mental health services by the time children reached age 3, at the end of the Early Head Start ͑EHS͒ program. This paper presents recent findings from the follow-up study in the spring prior to the children entering kindergarten, when a positive program impact emerged for reducing maternal depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 24 publications
1
53
0
2
Order By: Relevance
“…This finding is in line with previous research establishing high rates of depression among young mothers enrolled in HV programs. 57,58 Nevertheless, this is concerning given mounting evidence that maternal depression attenuates or dilutes treatment impact. 22,39 Although some studies suggest that HV can reduce maternal depression, 57 and that it is a promising intervention for reaching depressed parents who might not otherwise gain access to the help they need, 44 the results of large-scale evaluations generally indicate that parental depression is a serious impediment to HV program effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with previous research establishing high rates of depression among young mothers enrolled in HV programs. 57,58 Nevertheless, this is concerning given mounting evidence that maternal depression attenuates or dilutes treatment impact. 22,39 Although some studies suggest that HV can reduce maternal depression, 57 and that it is a promising intervention for reaching depressed parents who might not otherwise gain access to the help they need, 44 the results of large-scale evaluations generally indicate that parental depression is a serious impediment to HV program effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Nevertheless, this is concerning given mounting evidence that maternal depression attenuates or dilutes treatment impact. 22,39 Although some studies suggest that HV can reduce maternal depression, 57 and that it is a promising intervention for reaching depressed parents who might not otherwise gain access to the help they need, 44 the results of large-scale evaluations generally indicate that parental depression is a serious impediment to HV program effectiveness. 21 Our study findings also revealed an association between maternal depression and child maltreatment, though the relation differed for mothers who received HV comparedwith mothersinthe control group.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 La depresión no tratada durante el embarazo y el período posparto está asociada con resultados negativos para las madres, los bebés y las familias. Por ejemplo, la depresión durante el embarazo puede afectar el cuidado personal materno y reducir la probabilidad de que las mujeres reciban una atención prenatal adecuada.…”
Section: Un Llamado a La Capacitación Integral De Psicoterapia Perinatalunclassified
“…Por otra parte, si bien un estudio previo sobre la efectividad del modelo DIT no detectó efectos signifi cativos sobre la salud mental materna (Palmeros, Rojas & Traverso, 2008), un estudio reciente que evaluó los programas de intervención temprana Early Head Start, mostró que los efectos sobre la salud mental materna -específi camente la depresión en las madres-no eran detectables inmediatamente, sino que una vez transcurridos cerca de dos años con posterioridad a la intervención (Chazan-Cohen et al, 2007). En este sentido, resulta imperativo incentivar el desarrollo de nuevas investigaciones en programas de intervención temprana en la realidad latinoamericana, por ejemplo, que permitan identifi car efectos a mediano y largo plazo, y no solo al cierre de los procesos de intervención.…”
Section: Discusión Y Conclusionesunclassified